2020
DOI: 10.1017/s1366728919000798
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory brain dynamics of pronoun processing in native Spanish speakers and in late second language learners of Spanish

Abstract: A longstanding question in the second language acquisition literature is whether late second language (L2) learners process grammatical structures in a native-like manner. Here, we use Time Frequency Representation (TFR) analysis to test morpho-syntactic processing of clitic pronouns in native and late L2 learners of Spanish. The TFR results show overall similar power decreases in theta, alpha, and beta frequencies in both groups. Critically, the observed oscillatory effects persisted in time for native Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…This demonstrates the plasticity of the phonological encoding process in bilingual speakers, which depends essentially on years of L2 use rather than L2 AoA. The current findings, together with previous studies which reported aspects of bilingual processing independent of L2 AoA (e.g., De Carli et al, 2015; Rossi & Prystauka, 2020), imply that it is never too late to learn an L2.…”
Section: Discussionsupporting
confidence: 76%
“…This demonstrates the plasticity of the phonological encoding process in bilingual speakers, which depends essentially on years of L2 use rather than L2 AoA. The current findings, together with previous studies which reported aspects of bilingual processing independent of L2 AoA (e.g., De Carli et al, 2015; Rossi & Prystauka, 2020), imply that it is never too late to learn an L2.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, a considerable proportion of work examining the oscillatory correlates of higher-order language processing have not explicitly accounted for modulations in broadband aperiodic activity (e.g., Bonhage et al, 2017; Corcoran et al, 2022; Kepinska et al, 2017; Lewis et al, 2016; Mai, Minett, & Wang, 2016; Prat et al, 2016; Rossi & Prystauka, 2020; c.f., Cao et al, 2022), making it difficult to determine whether oscillatory activity parsimoniously explains behavioural outcomes. By separating oscillatory and aperiodic components, we have demonstrated that the aperiodic exponent flattens across time, while, for example, theta and alpha power increase across time throughout the language learning phase.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent view on the functional role of the alpha rhythm during cognition is that it is involved in gating information processing away from task-irrelevant regions, to the task relevant (Van Diepen et al, 2019). This technique has been used less frequently within the bilingualism literature to measure brain activity (but see Rossi & Prystauka, 2020), but we will elaborate on the potential of EEG for future research later in this review.…”
Section: Measuring Neurocognitive Adaptations In Bilingualsmentioning
confidence: 99%